Modal Analysis of 27 mm Piezo Electric Plate for Small-Scale Underwater Sonar-Based Navigation - M. O. Afolayan; D. S. Yawas; C. O. Folayan; S. Y. Aku (Journal of Engineering)
This work presents progress towards the development of a small-scale, purely sonar-based navigation device for a robotic fish (~394 mm long). Aperture overloading of small (5 mm diameter) ultrasonic transmitters does not allow them to be used effectively inside water. A test on a 27 mm diameter buzzer piezo plate shows promising performance under water at frequencies from 4.5 kHz to 80 kHz. ANSYS-based simulation was therefore used to find modal frequencies at higher frequencies so as to optimize this encouraging result. The simulation process also discovered several antiresonant frequencies such as 38.5 kHz, 54 kHz, and 57.5 kHz. All frequencies above the 8th harmonic (10,589.02 Hz) are out of phase with the input load except a resonance frequency of 42.5 kHz and an antiresonance frequency of 56.5 kHz. Also, the first harmonic (1,648.73 Hz) is the only frequency that gave a nodal deformation.